Realizing the City of Education Vision in The Study of Inclusive Education Policy Implementation in Metro City - Yuditya Wardhana Wardhana; Syeni Syeni; Ari Gusnita (Sawala : Jurnal Administrasi Negara, 2022)
Inclusive education is an education policy program that provides opportunities for children with special needs or disabilities to be accessible in regular schools. The problems faced by the Metro City government in carrying out inclusive education are the lack of standardization of facilities and infrastructure in the management of inclusive education in regular schools, limited accessibility for children with special needs in getting education, low understanding of educators in schools regarding children with special needs, and there is no special budget from the Metro City government that supports inclusive education, so that when the implementation of the policy can not be said to be successful, while the Metro City Development Vision is the Realization of an Educated City. The method used in this research is a qualitative approach. The results of this study indicate that inclusive education has not been implemented optimally because there are still many obstacles and obstacles in its implementation. Therefore, maximum effort is needed in implementing inclusive education with good cooperation and coordination between institutions and policy implementing institutions.